Functionalization of Graphene Oxide Layers Simultaneously with Liquid Phase Exfoliation - Anjo, L.; Arshakyan, A.; Gasparyan, N.; Shahinyan, A. A.; Aleksanyan, E.; Margaryan, N.
Graphene oxide (GO) has garnered significant interest for its exceptional properties and potential applications in various fields. This study investigated the disparities between graphene oxide synthesized in an ammonia-acetone solution and graphene oxide synthesized in acetone using the exfoliation method. Raman spectroscopy, FTIR spectroscopy, and current-voltage characteristics analysis were employed to evaluate the samples. Raman spectroscopy analysis revealed distinct differences in the molecular composition and structural characteristics of the samples, as indicated by variations in the "D," "G," and "2D" peaks. FTIR spectroscopy identified various functional groups in both samples, with changes attributed to the presence of ammonium in one sample. Furthermore, the current-voltage characteristics analysis was conducted to assess the electrical properties of the graphene films. Results of the current-voltage characteristics analysis showed that the conductivity of the membranes obtained in an acetone medium was approximately an order of magnitude higher than that of the membranes obtained in an ammonia medium. This discrepancy suggests that the exfoliation in an acetone medium resulted in stronger doping of the graphene layers compared to the exfoliation in an ammonia solution. The linearity observed in the current-voltage characteristics can be attributed to the presence of a significant number of free electrons in the conduction band of the samples due to doping. These findings provide valuable insights into the structural, compositional, and electrical properties of graphene oxide synthesized using different methods and precursor solutions. Understanding these disparities is crucial for tailoring graphene-based materials to specific applications.
Keywords: Physics